EFFECTS OF Ehrlichia canis, Anaplasma phagocytophilum /Anaplasma platys AND Dirofilaria immitis INFECTIONS ON OXIDATIVE STRESS AND ANTIOXIDANT BALANCE IN DOGS - Abdullah Kayar; Mehmet Erman Or; Fatih Mehmet Kandemir; Banu Dokuzeylül; Lukasz Adaszek; Sefa Küçükler (Journal of Animal and Plant Sciences, 2024)
The aim of the study was to investigate changes in serum oxidant/antioxidant balance in dogs of different breeds and sex, which were infected with Ehrlichia, Anaplasma or Dirofilaria immitis. We also sought to analyze the impact of pathogen species and canine sex on the changes in oxidative stress markers, nitric oxide level, and hematological parameters. A total of 59 dogs of different breeds and sexes were included in the study. Forty-one dogs infected with either Dirofilaria immitis, Anaplasma or Ehrlichia formed the study group, while the control group comprised of 18 healthy dogs with negative test results. Serum nitric oxide (NO), total oxidant capacity (TOC) and total antioxidant capacity (TAC) levels were measured. Oxidative stress index (OSI) was determined by calculating TOC-to-TAC ratio. In dogs with Ehrlichia or Anaplasma positivity, circulating NO and TOC levels were found to have increased significantly while heartworm infection did not significantly alter TOC levels. A significant decrease in TAC was observed in all animals with positive test results for any pathogen. The results indicated that Anaplasma, Ehrlichia and Dirofilaria infections cause adverse effects on the host cell redox balance in dogs, however, sex has no impact on oxidative stress markers, nitric oxide level, or hematological parameters.
Keywords: Anaplasma spp.; Ehrlichia spp.; oxidative stress; TAC; TOC.